Cyclotriphosphazene-based epoxy resins with excellent mechanical and flame retardant properties. (18th November 2022) - Wang, Jiachen; Liu, Wei; Liu, Huan; Wang, Xiaodong; Wu, Dezhen; Zhang, Shuangkun; Shi, Shaowei; Liu, Weiwei; Wu, Zhanpeng
Abstract: The design, synthesis, and characterization of a novel epoxy monomer, CP-EP, which consists of nontoxic eugenol and nonflammable cyclotriphosphazene has been carried out in this work. Chemical structure of CP-EP was confirmed by nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS). Using 4, 4′-diaminodiphenylmethane + diethyltoluenediamine (DDM + DETDA), succinic anhydride (SA), or methylhexahydrophthalic anhydride (MeHHPA) as curing agent, three cyclotriphosphazene-based thermosets (CPTs) were produced, and non-isothermal curing behaviors were investigated by using dynamic differential scanning calorimetry. In comparison to the bisphenol-A epoxy resin, CPTs exhibit higher glass transition temperature, enhanced tensile/flexural strengths, and significantly improved nonflammability. UL-94 rating and limiting oxygen index (LOI) for CPTs were V-0 and 28% respectively. These observations suggest an effective approach for the preparation of a halogen-free epoxy thermosetting system. This approach may be used for the generation of high-performance fire-safe epoxy thermosets. Both environment and human health can benefit from the use of such materials. Graphical abstract: Image 1 Highlights: A novel phosphazene epoxy monomer (CP-EP) is efficient and controlled synthesized. Investigation of thermal curing kinetics of CP-EP indicate its high reactivity. All cyclotriphosphazene-based thermosets (CPTs) showed excellent nonflammability. Comparing to E44 thermosets, CPTs show higher mechanical and thermal properties.